Current Evidence of Chinese Herbal Constituents with Effects on NMDA Receptor Blockade - David T. Yew; Ping Chung Leung; Wai Ping Lam; Hong Chai Tang; Willmann Liang (MDPI AG, 2013)
NMDA receptor (NMDA-R) is an important molecular entity governing a wide range of functions in the central nervous system. For example, the NMDA-R is involved in memory and cognition, and impairment of both (as in Alzheimer's Disease) is attributed to NMDA-mediated neurotoxicity. With greater understanding of the NMDA-R structure, antagonists with varying degrees of binding-site and subtype selectivity have been developed and put into clinical use. Discovery of target-specific Chinese herbs have also been made in parallel. This article provides an overview of the known active sites on the NMDA-R, followed by a discussion of the relevant herbs and their constituents. Experimental evidence supporting the inhibitory role of the herbal compounds on the NMDA-R is highlighted. For some of the compounds, potential research directions are also proposed to further elucidate the underlying mechanisms of the herbs. It is envisaged that future investigations based on the present data will allow more clinically relevant herbs to be identified.